Affected and connected: feminist and psychological perspectives on emotion in social media. Issue 8 (17th November 2019) - Prøitz, Lin; Carlquist, Erik; Roen, Katrina
ABSTRACT: This article works across psychology and feminist media studies to offer an empirically grounded investigation of affective expression in social media. To work empirically with understandings of affect, and to examine affective engagements via social media, we explore Instagram fans' responses to the Norwegian TV series Skam (translation: "shame"). We draw on feminist theoretical perspectives on affectivity and emotion, and critical psychological perspectives on well-being. We ask: how are affect and emotion woven through contributors' expressions, what do contributors write about their sense of belonging, and what is hoped for through affective engagement? By analyzing contributors' writing about their experiences of how Skam has affected their lives, this study illustrates how contributors to social media produce the idea of life as radically open to transformation. This analysis demonstrates how passionately imagined connections create new opportunities for becoming and belonging.